Comparison of cognitive-behavioral therapy and acceptance and commitment therapy on cognitive flexibility in mothers with autistic children - Karim Behnamfar; Ali Reza Rajaei; Saeed Teymouri (Shahid Beheshti University of Medical Sciences, 2022)
Background: Mothers with autistic children encounter with many challenges due to their child's developmental problems. This study aims to compare the effect trainings of cognitive-behavioral therapy (CBT) and acceptance and commitment therapy (ACT) on cognitive flexibility of the mothers with autistic children. Methods: The present research is a quasi-experimental study as pretest and posttest with a control group, which was performed on mothers with autistic children in three autism rehabilitation centers of Mashhad in 2020-2021. 45 people designated by purposive sampling method and randomly settled in three groups of 15 people (2 groups as experimental and 1 group as control). The experimental groups underwent interventions of CBT and ACT in 8 sessions of ninety minutes; whereas, control group didn't undergo any training. All three groups completed the cognitive flexibility inventory (CFI) in the pretest and posttest. Statistical analyses were performed using SPSS 23 software and method of covariance analysis (ANCOVA). Results: The results indicated that both training methods of CBT and ACT significantly increased the cognitive flexibility of the mothers with autistic children (P <0.05). Based on the results of Tukey's test, CBT training was more effective on cognitive flexibility of the mothers with autistic children compared to ACT training. Conclusion: With regards to the more effectiveness of the CBT, this therapeutic intervention approach can be used to improve emotion regulation strategies and increase the cognitive flexibility the mothers with autistic children.